The potential of Massive Open Online Courses in the context of corporate training and development - Sillak-Riesinger, Bianca (Springer Gabler, 2017)
Bianca Sillak-Riesinger examines to what extent Massive Open Online Courses (MOOCs) can be used as a beneficial opportunity in Corporate Training and Development. In the scope of the empirical analyses, experts were interviewed and a survey with professionals who take part in job-related MOOCs was conducted. Conclusions and recommendations for action regarding a possible usage of MOOCs in corporate learning are drawn for decision makers in Corporate Training and Development. A guide for companies interested in implementing MOOCs is included in the appendix. Contents Overview and Platforms of Massive Open Online Courses (MOOCs) Usage of MOOCs in Corporate Training and Development Target Groups Researchers and students in the fields of business administration, management, human resources, personnel development and education Learning officers, personnel development managers, consultants and MOOC providers The Author Bianca Sillak-Riesinger studied Business Administration at Aschaffenburg University of Applied Sciences, and afterwards graduated as a Master of Arts in International Management from Worms University of Applied Sciences. She joined a known software company in 2014, and currently works as an Innovation Manager with a special focus on Learning and Training.
Keywords: Employees -- Training of.; Employees -- Coaching of.; MOOCs (Web-based instruction); elektronické knihy; electronic books